A Study of Digital Leadership of School Adminstrators under Phitsanulok Primary Educational Service Area Office 2
This research purpose to study the digital leadership of school administrators under the Phitsanulok Primary Educational Service Area Office 2, covering 97 schools. The researcher used the entire population as the data source, consisting of one school administrator per school and one teacher responsible for personnel affairs per school, selected through purposive sampling, totaling 194 respondents. The research instrument was a questionnaire on the digital leadership of school administrators under the Phitsanulok Primary Educational Service Area Office 2, based on a five-point Likert scale. This questionnaire had an Index of Item-Objective Congruence (IOC) of 0.60 or higher and a reliability coefficient of .986. The statistical methods used for data analysis included frequency, percentage, mean, and standard deviation. The research results found that: The research results revealed that the overall level of digital leadership among school administrators under the Phitsanulok Primary Educational Service Area Office 2 was high. When considering each aspect, the highest average score was found in the area of digital leadership vision, ( = 4.29, S.D.= .65) which was at a high level. This was followed by digital communication, ( = 4.26, S.D. = .83) also at a high level. The lowest average score was in the area of using digital technology tools, ( = 4.21, S.D. = .77) which was still at a high level. , number=2, journal=Academic MCU Buriram Journal, author=Lakum, Benjarat and Natun, Jaruwan, year=2025, month=Jun., pages=254–269